2019
DOI: 10.3122/jabfm.2019.04.180384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electronic Cigarettes on Smoking Reduction and Cessation in Korean Male Smokers: A Randomized Controlled Study

Abstract: Introduction: New approaches to electronic cigarettes (e-cigarettes) as a form of nicotine replacement therapy (NRT) may reduce the rates of tobacco-related disease and mortality. Therefore, we investigated the effect of e-cigarettes on smoking cessation compared with nicotine gum. Methods: A total of 150 subjects were randomly assigned to 2 groups and each was allocated a 12week supply of either e-cigarettes or nicotine gum. The continuous abstinence rate, 7-day point prevalence of abstinence, smoking reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(101 citation statements)
references
References 23 publications
2
99
0
Order By: Relevance
“…associated with significantly increased smoking cessation in randomized clinical trials of e-cigarettes as smoking cessation therapy. Nine RCTs [16][17][18][19][73][74][75][76][77] were included for analysis. In 7 of the 9…”
Section: Provision Of Free E-cigarettes Wasmentioning
confidence: 99%
See 2 more Smart Citations
“…associated with significantly increased smoking cessation in randomized clinical trials of e-cigarettes as smoking cessation therapy. Nine RCTs [16][17][18][19][73][74][75][76][77] were included for analysis. In 7 of the 9…”
Section: Provision Of Free E-cigarettes Wasmentioning
confidence: 99%
“…RCTs, the control group was provided free cessation aids 16,17,19,73,74,76,77 ; 2 RCTs provided the control group with smoking cessation counseling only. 18,75 In Figure 4 and Table 2).…”
Section: Provision Of Free E-cigarettes Wasmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis was an intention to treat in almost all of the studies. 14,22 -28 One study reported lost follow up at an early stage of allocation rather than after randomization 29 and one study reported that percent of patients lost to follow up are similar in all arms of the study. 30…”
Section: Methodsmentioning
confidence: 99%
“…Thankfully, the article includes specific handouts that can be used for provider training. In an article from Korean family physicians, Lee et al 17 undertook a randomized trial of e-cigarettes compared with nicotine gum to help people stop smoking. These data add another choice to the options for patients.…”
Section: Substance Usementioning
confidence: 99%